Lobbying, information transmission, and unequal representation - Johan Lagerlöf; Lars Frisell (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2004)
We study the effects of unequal representation in the interest-group system on the degree of information transmission between a lobbyist and a policymaker. Employing a dynamic cheap-talk model in which the lobbyist cares instrumentally about his reputation for truthtelling, we show that the larger is the inequality, the less information can credibly be transmitted to the policymaker. We also investigate the effects of inequality on welfare and discuss the welfare effects of institutions that increase transparency but which as well, as an unintended side-effect, lower the lobbyist's incentives for truthtelling. – – In diesem Papier wird untersucht, welche Wirkung die ungleiche Repräsentation in einem Interessengruppensystem auf den Grad an Informationsübertragung zwischen einem Lobbyisten und einem Politiker hat. Es wird ein dynamisches Modell für ,Cheap-talk' verwendet, in dem angenommen wird, dass der Lobbyist Wert auf seine Reputation als aufrichtiger Informationsvermittler legt. Dabei kann gezeigt werden, dass je größer die Ungleichheit im System, dem Politiker umso weniger Information glaubwürdig übermittelt werden kann. Darüber hinaus wird die Wohlfahrtswirkung der Ungleichheit untersucht und diskutiert, welche Effekte solche Institutionen haben, die zwar einerseits die Transparenz erhöhen, mit unerwünschtem Nebeneffekt aber den Anreiz für Lobbyisten, Informationen wahrheitsgemäß weiterzugeben, verringern.
Keywords: D72; D78; D82; 330; Lobbying; interest groups; reputation; information transmission; representation; inequality; bias